Reliability analysis of steel buildings considering the flexibility of the connections of the GFs. (October 2020) - Llanes-Tizoc, Mario D.; Reyes-Salazar, Alfredo; Ruiz, Sonia E.; Valenzuela-Beltrán, Federico; Bojorquez, Edén; Chávez, Robespierre
Abstract: A numerical study to evaluate the reliability of 3D steel buildings with moment-resisting frames (MRFs) at the perimeter and gravity frames (GFs) at the interior under the action of seismic loading, is carried out. To this aim, the median values (MV) of the maximum drifts (MD) and fragility curves are obtained. The reliability, expressed as the mean annual rate of exceeding (υ) particular values of MD, is calculated by using the probabilistic seismic hazard analysis format. Three models, representing steel buildings of low-, mid- and high-rise are considered. The interior connections are assumed to be, first perfectly pinned (PP) as considered in practical design, and then as semi-rigid (SR). The Beam-Line Theory together with The Model of Richard are used to represent the SR connections. Results indicate that the MV demands and the seismic fragility can be significantly reduced when the stiffness and dissipation of energy at interior connections are considered; reductions larger than 40% and 60%, respectively, are observed in many of the cases. The structural reliability is also significantly improved; reductions close to 20% in the expected maximum drift are observed in many cases. It is concluded that the effects of the stiffness and energy dissipation of the connections of GFs on the seismic response (in terms of MV), on the fragility curves, and on the mean annual rate of exceedance (υ), are significant so they should not be ignored. Even for shear connections whose contribution in practical design is totally ignored, the effect is considerable.